PENINGKATAN KEMAMPUAN BERPENDAPAT MAHASISWA MELALUI PROBLEM BASED LEARNING (PBL) SEBAGAI PENDUKUNG PENCAPAIAN KERANGKA KUALIFIKASI NASIONAL INDONESIA (KKNI) PADA MATA KULIAH PRAGMATIK - Syaifudin, Ahmad; Sulistyaningrum, Septina (Universitas Negeri Semarang, 2015)
This abstract aims to explain the improvement of studentsâ ability inÂ giving opinion in pragmatic subject through PBL model as a support of KKNI achievement. The research was conducted through the lesson study (LS) consisting Â of the stage plan, do, and see. Results of this study revealed that there are twoÂ factors that cause low ability to express their opinions, namely anxiety (fear)Â and lack of ability in understanding the material concept. Through PBL modelsÂ with LS system, studentsâ fear could be erased. It increased material conceptÂ understanding of the students. The increase was offset by an ability improvementÂ in expressing opinions as much as 91% of the number of students involved inÂ learning.Keywords: Problem Based Learning (PBL), KKNI